Konflik Kebudayaan Menurut Teori Lewis Alfred Coser Dan Relevansinya Dalam Upacara Pemakaman (Rambu Soloâ) Di Tana Toraja - Panggarra, Robi (Sekolah Tinggi Theologia Jaffray, 2014)
Tujuan penulisan ini adalah: untuk menganalisis sejauh mana konflik dalam budaya upacara kematian (Rambu Soloâ) Suku Toraja memberi dampak berjalannya fungsi AGIL (Adaptation, Goal attainment, Integration, dan Latency Patterns Maintenance) dengan baik ataupun memperkuat ingtegrasi di antara kelompok kaya dan miskin, atau kelompok bangsawan dan rakyat jelata ataupun kelompok hamba. Kebudayaan upacara Rambu Soloâ di Tana Toraja jelas memiliki nilai potensi konflik, akan tetapi beberapa nilai integrasi yang diungkapkan oleh Coser memang memberi pengaruh terhadap kesatuan masyarakat Tana Toraja. Di sisi yang lain juga memberikan pengaruh yang kuat terhadap kesatuan masyarakat Tana Toraja yang tentunya tidak dipahami oleh Coser, yaitu adanya nilai-nilai Tongkonan yang mengikat masyarakat untuk tidak berkonflik.Â Kata-kata kunci: konflik, kebudayaan, teori Lewis Alfred Coser, upacara, pemakaman, Rambu Soloâ, Tana TorajaThe aim of this writing is: to analyze how much the conflict which is in the cultural funeral ritual (Rambu Soloâ), of the Torajan ethnic group, impacts the function of AGIL (Adaptation, Goal Attainment, Integration, and Latency Patterns Maintenance) in a positive manner or evenstrengthens the integration between wealthy and poor groups, or between aristocratic groups and the common people or servants.Â The cultural ritual, Rambu Soloâ, in the Torajan region clearly possesses the potential for conflict, several integration values, however, which are noted by Lewis Alfred Coser, admittedly influence the unity of the Torajan community. Â There exists, however, another factor which strongly influences the unity of the community in the Torajan region which, in fact, was not understood by Coser; that is the presence of Tongkonan values which bind the community so that conflict does not occur.Â Keywords: conflict, culture, Lewis Alfred Coserâs theory, ritual, funeral, Rambo Soloâ, Torajan region